Iowa RBA, November 17, 1997 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1997)
Iowa RBA update for November 17, 1997. Highlights of the update include sightings of a female Surf Scoter, a Long-tailed Duck, Common Redpolls in four locations, and White-winged Crossbills in three locations. Also included are handwritten notes for the next week's update with sightings of a Bohemian Waxwing and a Eurasian Goldfinch. Epson - sheet feed/flatbed